Effect of Diamagnetic Ion Substitution on Structural and Magnetic Properties of Nd3+ Modified Solid Solutions. Issue 203 (22nd November 2019) - Kumar, Anil; Sharma, Preeti; Kumar, Sunil; Singh, Anupinder; Kundu, R. S.; Punia, Rajesh
Abstract: Solid solutions of Bi0.9 Nd0.1 Fe1− x Ti x O3 have been prepared using conventional solid state reaction route. The Rietveld refinements of XRD patterns of all samples confirm the rhombohedral structure at room temperature. With increase in Ti substitution, there is reduction in leakage current and improvement in ferroelectric properties in the studied Bi0.9 Nd0.1 Fe1− x Ti x O3 solid solutions. The ac conductivity follows the universal Jonscher's power law for all the samples. Antiferromagnetic orders are observed to be suppressed on Ti substitution, in the studied BNFO solid solutions, thereby, giving rise to non-zero magnetic moment. The remnant magnetization has been observed to increase with increase in Ti content.